The associations of AI assisted training on sport performance among student athletes based on a dual path chain mediation model with the moderating role of psychological adaptability - Zhang, Huiying; Sun, Junjun (Frontiers in Psychology, 2026)
PurposeThis study examines the associations between AI-assisted training and sport performance among student-athletes using a dual-path chain mediation framework. Specifically, it tests two hypothesized chain mediation pathways and examines the moderating role of psychological adaptability.MethodsA cross-sectional questionnaire survey was conducted among 600 student-athletes from universities in three Chinese provinces using convenience sampling. Structural equation modeling and moderated regression analysis were employed to analyze the data.ResultsAI-assisted training was significantly associated with higher sport performance, with evidence of a primary association (β = 0.124, 95% CI [0.091, 0.156], p = 0.0017) as well as weak additional associations transmitted through two chain mediation pathways—Path 1 (β = 0.003, 95% CI [0.002, 0.006], p = 0.0010) and Path 2 (β = 0.007, 95% CI [0.004, 0.011], p = 0.0012). The overall association was β = 0.135 (95% CI [0.101, 0.166], p = 0.0017). In addition, psychological adaptability was positively associated with the strength of this relationship, as reflected by a significant interaction term (β = 0.115, 95% CI [0.091, 0.138], p < 0.001).ConclusionAI-assisted training was associated with higher sport performance both directly and indirectly through two conceptual pathways—cognitive-skill and behavioral-psychological processes. Moreover, the strength of these associations varied as a function of athletes' psychological adaptability, indicating a significant moderating role.